Imbalanced Gamma-band Functional Brain Networks of Autism Spectrum Disorders. (21st August 2022) - Wang, Chen-Guang; Feng, Chun; Zhou, Zheng-Rong; Cao, Wen-Yue; He, Dan-Jun; Jiang, Zhong-Li; Lin, Feng
Highlights: Brain activity is suppressed at the gamma-band level in children with autism. Distribution and intensity of the information flow in autistic children's brain network is aberrant. Connectivity of right Heschl's gyrus is associated with clinical manifestations in children with autism. Abstract: Resting gamma-band brain networks are known as an inhibitory component in functional brain networks. Although autism spectrum disorder (ASD) is considered as with imbalanced brain networks, the inhibitory component remains not fully explored. The study reported 10 children with ASD and 10 typically-developing (TD) controls. The power spectral density analysis of the gamma-band signal in the cerebral cortex was performed at the source level. The normalized phase transfer entropy values (nPTEs) were calculated to construct brain connectivity. Gamma-band activity of the ASD group was lower than the TD children. The significantly inhibited brain regions were mainly distributed in the bilateral frontal and temporal lobes. Connectivity analysis showed alterations in the connections from key nodes of the social brain network. The behavior assessments in the ASD group revealed a significantly positive correlation between the total score of Childhood Autism Rating Scale and the regional nPTEs of the right transverse temporal gyrus. Our results provide strong evidence that the gamma-band brain networks of ASD children have a lower level of brain activities and different distribution of information flows. Clinical meanings of such imbalances of both activity and connectivity were also worthy of further explorations.